The influence of emotion with the development of Vitiligo disease / A influência da emoção com o desenvolvimento da doença Vitiligo - Sheylla Acacio dos Santos; Cleis Nunes Santos; Jaqueline Maria da Silva (Universidade Estadual de Alagoas, 2018)
Vitiligo is a chronic systemic disease, acquired from an unpredictable clinical evolution characterized by the appearance of maculas and spots in areas of the skin and mucous membranes with a tendency to increase significantly in size, due to the absence of melanin due to disappearance of the melanocytes in the affected area. Its cause and its biochemical mechanism of action are unknown. The main objective is to describe the action of the emotional state in the development of vitiligo disease in patients; thus facilitating the description of the changes that the feelings can cause in the development of this dermatosis. This is a descriptive bibliographical review, which seeks to expose the relationship of the emotional state in the development of vitiligo disease. The disease directly affects the production of melanin through the melanocytes that are cells derived from the neural crest. In most patients with vitiligo, the diagnosis is made by clinical examination followed by analysis of the depigmented area under the light of Wood. The treatment has some variants, since it has as characteristic to be based in the complexity, in the extension of the manifestation and still depends on the psychological state and mainly of the color of the skin. Thus, the feelings of rejection, shame, frustration and sadness allied to stress can generate a very relevant factor in the development of vitiligo disease. This is because it is directly connected with the nervous system, which in turn, the increase of these feelings raises in the production of neurotransmitter and neuroendocrine hormones, responsible respectively for the transmission of stimuli and regulation of the organism.